G424(P) Re-interpreting the appropriate growth hormone response to hypoglycaemia. (25th October 2020) - Khan, UA; Wong, FY; Azam, S; Blake, O; Murphy, AM; Neylon, OM; O'Gorman, CS
Abstract : Aims: 'Critical samples' consist of assessment of an individual's metabolic and endocrine status during a hypoglycaemia episode to evaluate for a pathological contributor towards aetiology of the episode. Growth hormone (GH) level is part of this work up to assess likelihood of GH deficiency. The aim of this study was to identify if the preset cut off value for growth hormone '7 microgram/Litre' during hypoglycaemia is appropriate and how likely values below this are to be indicative of growth hormone deficiency. Methods: The study population consisted of paediatric patients aged up to 16 years old who had critical samples sent during hypoglycaemia over a 12 month period from 1st Jan 2018 until 30th Dec 2018 inclusive at University Hospital Limerick. Retrospective review from a prospectively collected database of glucose and GH levels as well as other growth parameters. Results: Forty blood samples were collected during the study period during hypoglycaemia. One sample was insufficient for analysis of GH level and of the remaining 39, only three (7.6%) patients exhibited a 'normal' GH response to hypoglycaemia of ≥7 mcg/L and thirty-six patients (92%) had suboptimal GH levels. Data was skewed to the right with median GH reading of 3.19 mcg/L. The available data on the other parameters i.e. Insulin-like Growth Factor (IGF)-1 levels, Growth Velocity/Height centiles and Growth hormone stimulation test (GHST) was limited but normal. Conclusion: No patient had documented GH deficiency or loss of height centiles, despite only 7.6% (3/39) having 'adequate' GH response during hypoglycaemia. These data suggest that the optimal level for GH during hypoglycaemia should be re-evaluated in larger prospective studies, to reduce unnecessary evaluation for GH deficiency with attendant anxiety and cost generated therein.